STUDY AND ANALYSIS OF ENERGY BANDS WITH VARIOUS TYPES OF CRYSTAL STRUCTURES - Kumrey, G.R.; Mahobia, S.K. (International Journal of Engineering Technologies and Management Research, 2016)
The difference between conductors, insulators and semiconductors is to plot the available energies for electrons in the materials. Instead of having discrete energies as in the case of free atoms, the available energy states form bands. Energy bands occur in solids where the discreet energy levels of the individual atoms merge into bands which contain a large number of closely spaced energy levels.